STUDY ON SEVERAL REPRODUCTIVE ASPECTS OF SOFT CORAL SINULARIA FLEXIBILIS QUOY & GAIMARD IN BARRANG LOMPO ISLAND, SPERMONDE ARCHIPELAGO, MAKASSAR CITY - Abdul Haris - (Bionatura, 2011)
Sinularia flexibilis is one species of soft coral having high economic value due to its pharmaceutical content. This research was aimed to analyze several reproductive aspects of this soft coral using direct observation in its natural habitat, periodically collecting samples of body tissues, and then preparing and observing its histological preparation. Reproductive aspects found in this research were analyzed descriptively. Results of this research showed that the sexuality type of soft coral S. flexibilis was simultaneous hermaphrodite reproducing by spawning, its reproductive pattern was hermaphrodite followed by spawning. It spawned from May-September, and the development of its sperm and oocyt was divided into four stages with different characters between one to another, particularly differed in shape, presence of organelles, and organelle colors.Keywords: Sinularia flexibilis, reproduction, Barrang Lompo Island